Translating Evidence into Healthcare Policy and Practice: Single Versus Multi-Faceted Implementation Strategies - Is There a Simple Answer to a Complex Question? - Gill Harvey; Alison Kitson (Kerman University of Medical Sciences, 2015)
How best to achieve the translation of research evidence into routine policy and practice remains an enduring challenge in health systems across the world. The complexities associated with changing behaviour at an individual, team, organizational and system level have led many academics to conclude that tailored, multifaceted strategies provide the most effective approach to knowledge translation. However, a recent overview of systematic reviews questions this position and sheds doubt as to whether multi-faceted strategies are any better than single ones. In this paper, we argue that this either-or distinction is too simplistic and fails to recognize the complexity that is inherent in knowledge translation. Drawing on organizational theory relating to boundaries and boundary management, we illustrate the need for translational strategies that take account of the type of knowledge to be implemented, the context of implementation and the people and processes involved.